(untitled) (Nordic Journal of African Studies, 2009)
This paper examines the cultural and socio-economic profiles of porters in Accra, capital of Ghana. Porters are individuals who carry goods in and around markets and commercial centers in cities for a fee. A majority of the porters migrate from northern or rural parts of the country to live and work in southern cities. Findings indicate that porters have very little or no education and are from very poor socio-economic backgrounds. Male porters tend to be slightly older, have a little education, married and living with their families in Accra. Female porters are younger, temporary porters, and in addition to low socio-economic background are affected by cultural factors.